2013
DOI: 10.1177/0956797612470958
|View full text |Cite
|
Sign up to set email alerts
|

Gist Memory in the Unconscious-Thought Effect

Abstract: The unconscious-thought effect (UTE) occurs when people are better able to make complex decisions after a period of distraction rather than immediately or after a period of conscious deliberation. This finding has often been interpreted as evidence of unconscious thinking. In two experiments, we provided the first evidence that the UTE is accompanied by enhanced memory for the gist of decision-relevant attributes and demonstrated that the cognitive demands of a distraction task moderate its effect on decision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 34 publications
2
59
1
2
Order By: Relevance
“…For example, Lerouge (2009) reported that participants who were primed to have a configural mind-set benefited from unconscious thought in differentiating alternative choices, whereas those with a featural mind-set did not. Lerouge suggested this is because a configural mind-set motivates participants to form evaluatively coherent representations of choices, which are more compatible with the ''gist-based'' process of unconscious thought (Abadie et al, 2013;Dijksterhuis et al, 2009). However, the current findings illustrate that wholists, who have a natural preference for holistic organization of information, did not manifest the deliberation-without-attention effect; they performed as well without as with distraction when differentiating complex choices.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…For example, Lerouge (2009) reported that participants who were primed to have a configural mind-set benefited from unconscious thought in differentiating alternative choices, whereas those with a featural mind-set did not. Lerouge suggested this is because a configural mind-set motivates participants to form evaluatively coherent representations of choices, which are more compatible with the ''gist-based'' process of unconscious thought (Abadie et al, 2013;Dijksterhuis et al, 2009). However, the current findings illustrate that wholists, who have a natural preference for holistic organization of information, did not manifest the deliberation-without-attention effect; they performed as well without as with distraction when differentiating complex choices.…”
Section: Discussioncontrasting
confidence: 65%
“…Evidence has suggested that evaluatively coherent representations enhance the differentiation among choices (Judd & Lusk, 1984;Liberman & Chaiken, 1991;Millar & Tesser, 1986). This characteristic of unconscious thought was further supported by two more recent studies, which reported that unconscious thought is accompanied by an enhancement of gist memory of decision-relevant attributes (Abadie, Waroquier, & Terrier, 2013) and is more effective in weighting important attributes (e.g., good safety record for a car) over unimportant attributes (e.g., availability of colors for a car; Bos et al, 2011). All suggested that unconscious thought, relative to conscious thought, is more capable of integrating decision-relevant information into better organized, holistic representations, thus improving decision-making.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…One explanation could be that mind wandering is useful for individuals. In a recent study by Abadie et al (2013), participants had to give their response to a complex problem immediately or after a delay during which they had to perform a distractive task. The solution given to the problem was better for participants who performed a distractive task before answering the problem.…”
Section: Discussionmentioning
confidence: 99%
“…In conducting such a test, it seems useful to glean insights from fundamental research on memory representations to better understand how the depth of processing at intake relates to the completeness of the representation on which later task performance is based. The distinction between verbatim and gist memory seems especially relevant (e.g., Abadie et al 2013;Reyna 2012;Reyna and Brainerd 1995). That is, the repetition of a procedure might have a strong effect on verbatim memory development, which refers to a detailed representation of the exact information.…”
Section: Discussionmentioning
confidence: 99%